Changes in the relationship between temperature during the seed‐filling period and soya bean seed isoflavones under water‐deficit conditions - Carrera, Constanza Soledad; Dardanelli, Julio Luis (Blackwell, 2018)
Isoflavones have been shown to have health‐promoting activities in humans and are particularly abundant in soya bean. This study was conducted to determine how water deficit during seed fill affects the already known relationship between temperature and, alternately, solar radiation with soya bean seed isoflavone content. Isoflavone profile was analysed from seed samples of commercial cultivars grown in 76 environments in Argentina (29–38°S). Significant explanatory multiple linear regressions were detected for total isoflavones (TI), aglycones (AGL), glucosides (GLC), malonyl glucosides (MAL) and acetyl glucosides (ACE) regarding the following: temperature during seed fill (TmR5R7) and precipitation minus potential evapotranspiration during the reproductive period (pp‐PETR1R7), as well as for the combinations of these climatic variables. Cumulative solar radiation predicted isoflavone content but was less robust than TmR5R7 and pp‐PETR1R7. To our knowledge, this is the first report of changes in the relationship between TI, as well as AGL, GLC, MAL, and ACE and TmR5R7 as a function of drought in the field. When pp‐PETR1R7 was below 70 mm (indicating drought), TI, as well as AGL, GLC, MAL, and ACE decreased linearly with rising temperatures and with increasing water deficit (decreasing values of pp‐PETR1R7), with both climatic variables exhibiting additive effects on isoflavones. Our results also suggest that water deficit (estimated by pp‐PETR1R7) would be important for modelling the relationship between temperature and soya bean seed isoflavones in rainfed crops.